CHARACTERIZATION OF Y2O3:EU COATED WITH POLYSTYRENE - Cui H.; Hong G. (My University, 2000)
The core-shell Y2O3:Eu3+/polystyrene particles was prepared by surface modification with citric acid and emulsion polymerization method of styrene. The DTA curve of coated particles exhibits a small and wide exothermic peak of organic compound around 387°C. The carbonyl stretching vibration band was shifted to low wavenumber in FTIR spectrum and the binding energy of Y3d5/2 was shifted to high-energy band in XPS spectrum. The results of FTIR and XPS show that citric acid was coupled to the particles surface. The hydrophilic surface became amphiphilic by modification of citric acid. So styrene could adsorb on particles surface to form emulsion structure which inorganic core was inside. EDS spectra show that Y2O3:Eu3+ particles were coated uniformly with polystyrene.